CMIP5 Intermodel Relationships in the Baseline Southern Ocean Climate System and With Future Projections. Issue 6 (24th June 2021) - Kajtar, Jules B.; Santoso, Agus; Collins, Matthew; Taschetto, Andréa S.; England, Matthew H.; Frankcombe, Leela M.
Abstract: Climate models exhibit a broad range in the simulated properties of the climate system. In the early historical period, the absolute global mean surface air temperature in Coupled Model Intercomparison Project, Phase 5 (CMIP5) models spans a range of ∼12°C – 15°C. Other climate variables may be linked to global mean temperature, and so accurate representation of the baseline climate state is crucial for meaningful future climate projections. In CMIP5 baseline climate states, statistically significant intermodel correlations between Southern Ocean surface temperature, outgoing shortwave radiation, cloudiness, the position of the mid‐latitude eddy‐driven jet, and Antarctic sea ice area are found. The baseline temperature relationships extend to projected future changes in the same set of variables, impacting on the projected global mean surface temperature change. Models with initially cooler Southern Ocean tend to exhibit more global warming, and vice versa for initially warmer models. These relationships arise due to a "capacity for change". For example, cold‐biased models tend to have more cloud cover, sea ice, and equatorward jet initially, and thus a greater capacity to lose cloud cover and sea ice, and for the jet to shift poleward under global warming. A first look at emerging data from CMIP6 reveals a shift of the relationship from the Southern Ocean towards the Antarctic region, possibly due to reductions in Southern Ocean biases, such as in westerly wind representation. Plain Language Summary: Modern simulations of the Earth's climate system differ in some of their large‐scale features. For example, in models reported on by the Intergovernmental Panel on Climate Change in the Fifth Assessment Report, the global average temperature ranges between 12°C and 15°C. Global mean temperature is known to be linked to other features, such as wind, clouds, and rainfall. Accurately modeling the present‐day climate is important, so that we can have more confidence in the possible futures they simulate under different levels of anthropogenic greenhouse gas emissions. In this study, strong relationships are found between simulated Southern Ocean temperature and the amount of sea ice and clouds. In addition, it is found that the initial Southern Ocean temperature is also related to changes in sea ice and cloud simulated in the future. A model that is cooler initially, for example, tends to have more sea ice and cloud, but also loses more sea ice and cloud in the future, and simulates more global warming. Key Points: There are robust intermodel correlations across elements of the Southern Ocean climate system in historical Coupled Model Intercomparison Project, Phase 5 (CMIP5) simulations The baseline Southern Ocean temperature relationship extends to projected changes in radiation, cloudiness, the jet latitude and sea ice CMIP5 models with initially cooler Southern Ocean exhibit more global warming, likely due to greater capacity for change